SOCIAL-CONTROL OF GROWTH IN FISH - Volpato, G. L.; Fernandes, M. O. (Associação Brasileira de Divulgação Científica (ABRADIC), 1994)
This review concerns the phenomenon of heterogeneous growth (Het-G) in fish. Het-G is characterized by different growth rates between conspecifics. Although genetic determination on Het-G is recognized, grouping increases the difference in size between conspecifics. This review focuses on population factors and the mechanisms underlying the socially mediated Het-G are summarized and discussed. The aim of this paper is to arrive at a general statement explaining why grouping decreases mean growth and why it suppresses growth only in some individuals. The mechanisms described are: a) food competition, b) chemical factors released by conspecifics, and c) social stress. Social stress is analyzed in terms of the effect on appetite, digestive processes and metabolism. It is proposed that the predominant mechanism promoting socially mediated growth suppression is related to the social habit of the species. The biological significance of growth heterogeneity in fish is also discussed. Growth variability is suggested as an adaptative strategy to optimize survival of the population in a restricted space.
Keywords: FISH; STRESS; SOCIAL STRESS; GROWTH; GROWTH VARIABILITY; GROUPING